Pengaruh Faktor Sosial Ekonomi Terhadap Angka Kematian Bayi (AKB) Pada Kabupaten/Kota di Propinsi Jawa Timur - Fadjar Suhaeri; Lilik Sugiharti (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2020)
Infant Mortality Rate (IMR) is one indicator of health development. IMR of East Java Province showed its success in reducing IMR, but if considered in each regency in East Java province was still among the high, in addition there were still 21 municipal regencies that still exceeded the 2014-2019 RPJMD target of East Java Province. This study tries to analyze the socioeconomic factors of the Infant Mortality Rate in East Java Province. This study uses a panel data regression, using panel data 38 city districts in East Java. This study uses independent variables: PDRB per capita, Mean Years School of Women, length of time supporting breastfeeding, percentage of households that require up to 30 minutes, number of posyandu, number of medical personnel, number of paramedics and immunization. The results of the regression test showed that the overall variable was the infant mortality rate in East Java Province, but only the variables gave breastfeeding and the number of medical workers who did not match the infant mortality rate in East Java Province.